2008
DOI: 10.1007/s10156-008-0648-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive detection of causative pathogens using real-time PCR to diagnose pediatric community-acquired pneumonia

Abstract: We have developed a real-time reverse transcription-PCR (RT-PCR) method to detect 13 respiratory viruses: influenza virus A and B; respiratory syncytial virus (RSV) subgroup A and B; parainfluenza virus (PIV) 1, 2, and 3; adenovirus; rhinovirus (RV); enterovirus; coronavirus (OC43); human metapneumovirus (hMPV); and human bocavirus (HBoV). The new method for detection of these viruses was applied simultaneously with real-time PCR for the detection of six bacterial pathogens in clinical samples from 1700 pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 44 publications
7
89
2
4
Order By: Relevance
“…It has been suggested that respiratory viruses, especially rhinovirus and respiratory syncytial virus (RSV), are associated with IPDs in children that do not attend day-care centers (18). Hasegawa et al have reported that RSV is detected mainly during late summer to winter in cases of pediatric community-acquired pneumonia in Japan (19). The increasing prevalence of pneumococcal colonization we identified in autumn may have been associated with the prevalence of such respiratory infections.…”
Section: Discussionmentioning
confidence: 68%
“…It has been suggested that respiratory viruses, especially rhinovirus and respiratory syncytial virus (RSV), are associated with IPDs in children that do not attend day-care centers (18). Hasegawa et al have reported that RSV is detected mainly during late summer to winter in cases of pediatric community-acquired pneumonia in Japan (19). The increasing prevalence of pneumococcal colonization we identified in autumn may have been associated with the prevalence of such respiratory infections.…”
Section: Discussionmentioning
confidence: 68%
“…Legionella pneumophila was exceedingly rare in children, with only 1 case in 1,765 patients with CAP. 52,56 The overall prevalence in adults was 2.8% (95% CI, 2.1%-3.6%), although in most studies it was between 1% and 3%. Again, there was significant heterogeneity.…”
Section: Resultsmentioning
confidence: 98%
“…Though the therapeutic implications of interactions between bacteria and platelets are still being explored, some specialists think that the antibacterial potential of platelets could be utilized by selectively releasing, or mimicking, thrombocidins which are microbicidal proteins found in the human blood platelets [15] .…”
Section: Discussionmentioning
confidence: 99%